ANALISA FAKTOR-FAKTOR PEMBAURAN ANGGOTA KELOMPOK TANI DI KAMPUNG WARIORI DISTRIK MASNI KABUPATEN MANOKWARI - Jouvial Kalalo; Yolanda Holle; Palinggi, Yunita (Sosio Agri Papua, 2024)
Social integration in agricultural environments occurs when farmers form farmer groups to collaborate in farming activities, processing results, and marketing. Through these farmer groups, members can support each other, share information, and collectively improve farmers' welfare. A concrete example of this integration within farmer groups is collaboration in agricultural activities; group members often work together on various farming tasks, such as planting, caring for crops, and harvesting. This study aims to identify the factors influencing integration within farmer groups in Masni District. The research was conducted over a month, from April to May 2024. The research location was chosen based on an initial survey showing that there are group members from Papua, NTT, and Java living together and interacting in the village. The research method used is Explanatory. Based on the research results conducted in Wariori Village, the integration process among farmer group members impacts forms of integration such as crosscultural marriages. This is because group members mix, facilitating and smoothing social adaptation, which eventually leads to tolerant social relationships and interactions within the community as expected. The community's ability to build good relationships positively affects interactions in the village environment, allowing integration between the two groups to proceed harmoniously and with tolerance. In their farming activities, farmers also interact with each other, gathering and blending to achieve common goals and interests through discussions or sharing experiences related to land management and cultivation activities.